Cornelius Nepos’ Lebensbeschreibungen und ihre Bedeutung angesichts Theorie und Kritik der Biographie in Antike und Moderne - Mehl, Andreas (Anabasis. Studia Classica et Orientalia, 2020)
In continuation of the research in the last decades, the author deals with additional features of Nepos’ biographies which in general bear positive testimony for their literary and historical quality. The author at first examines Nepos’ biographies for characteristics that are both, formal and regarding content and then, with regard also to ancient historical writing, puts Nepos’ biographies themselves and his theoretical thoughts about biography in the spheres of ancient as well as modern theories and critics of historical biography. The evident rivalry between ancient biography and historiography is explained by the overlapping interests of both sides in individual behaviour. Nepos is shown as an author confident of the value of biography and moreover as an ancient biographer whose theoretical position and biographical writing are near to modern biography with its sociological background.